Kualitas Kepemimpinan Nasional Dalam Mewujudkan Pemerintahan Yang Bersih Guna Tercapainya Tujuan Nasional - Santoso, Bibit (Sekolah Tinggi Ilmu Pemerintahan Abdi Negara, 2017)
In the field of defense and security, the threat of disintegration, crime and the high quality and quantity, the spread of drug traficking and smuggling and illegal trade are difficult of eradicate. The condition of our nation is currently facing a very powerful test, not because it is only a multidimensional crisis, but also involves the loss of obedience, the role model of its leaders hopes that this nation will soon get candidates for national leaders who are not only strong leaders (Strong Leader) ad a fusion of manager character leaders (leaders) and statesmen (statesman) with international standards but also a personal